Права третьої особи, щодо майна якої вирішується питання про арешт, у кримінальному провадженні - Смалюк, Т.; Smaliuk, T. (Східноєвропейський національний університет імені Лесі Українки, 2019)
У статті досліджуються права третьої особи, щодо майна якої вирішується питання про арешт. Обґрунтовується, що не всі з наведених прав третьої особи, щодо майна якої вирішується питання про арешт, можна віднести до тих прав, які безпосередньо стосуються арешту майна. Деякі права пропонується уточнити. Зроблено висновок, що у кримінальному процесуальному законі потрібно навести вичерпний перелік прав третьої особи, щодо майна якої вирішується питання про арешт слідчим суддею, а також при проведенні подальшого досудового розслідування і судового розгляду. Запропонована авторська редакція ч. 2 ст. 64-2 КПК України.The article interprets the controversial issues concerning the legal status of a third person on whose property the question of arrest is being considered. The author criticizes Article 64-2 of the CPC of Ukraine and indicates to its textual shortcomings, and suggests his own author's editing of Part 2 of Article 64-2 of the CPC of Ukraine. The study argues that not all of the rights of a third party whose property is under the decision of confiscation can be attributed to those rights that directly relate to the seizure of property. Some rights are to be specified. The author concludes that the criminal procedural law should provide an exhaustive list of the rights of a third party, on whose property the question of arrest is being considered by an investigating judge, and further in the pre-trial investigation and litigation. The introduction of amendments to the CPC, proposed by the author, will significantly improve the provisions of criminal procedural legislation on the procedural rights of a third party, on whose property the question of arrest is being considered.
Rights of a Third Party Whose Property is under the Decision of Arrest in Criminal Proceedings
Keywords: третя особа; арешт майна; права; накладення арешту; спеціальна конфіскація; процесуальні права; представник третьої особи; third party; seizure of property; rights; arrest; special confiscation; procedural rights; third party representative